Sự biến đổi năng lượng hoạt hóa và ảnh hưởng của xúc tác axit Lewis BF3 trong phản ứng Diels – Alder của isopren với các dẫn xuất etylen - Thọ, Nguyễn Hữu; Phong, Võ Thành (Vietnam Journal of Chemistry, 2016)
The Diels-Alder cycloaddition reactions of isoprene with derivatives of ethylene were studied by the Density Functional Theory using the B3LYP functional and the 6-311 ++ G (d, p) basis set. In this paper, our result shows that the activation energy of the reactions is correlated linearly with the total deformation energy of the diene and dienophile components. In the presence of the Lewis acid catalyst BF3, the activation energy is decreased because of reducing of HOMO and LUMO distance which is derived from orbital interaction. Keywords. Diels-Alder, DFT, FMO, cycloaddition reaction, isoprene.